2014
DOI: 10.1155/2014/190945
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Level and Oxidative Stress Contribute to Obesity-Induced Low Testosterone in Murine Testicular Tissue

Abstract: Objective. This study evaluated the effects of obesity on the function of reproductive organs in male mice and the possible mechanism of male secondary hypogonadism (SH) in obesity. Methods. Ninety-six mice were randomly assigned to three groups: the control group, diet-induced obesity group, and diet-induced obesity resistant group for 8 weeks and 19 weeks. The effects of short- and long-term high-fat diet on the reproductive organs were determined by measuring sperm count and motility, relative testis weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 48 publications
4
83
0
1
Order By: Relevance
“…Thus, increased adiposity would result in increased activity of aromatase and thereby increased metabolism of testosterone to estrogens (Blouin et al, 2006). Additionally, male mice maintained on HFD have decreased testosterone levels associated with apoptosis of Leydig cells in the testes and reduced testicular weight and function (Zhao et al, 2014). Thus, it is likely that both, increased metabolism of testosterone in adipose tissue and decreased testosterone production in the testes, are mechanisms by which obesity drives testosterone loss.…”
Section: Sex Differences In Obesitymentioning
confidence: 99%
“…Thus, increased adiposity would result in increased activity of aromatase and thereby increased metabolism of testosterone to estrogens (Blouin et al, 2006). Additionally, male mice maintained on HFD have decreased testosterone levels associated with apoptosis of Leydig cells in the testes and reduced testicular weight and function (Zhao et al, 2014). Thus, it is likely that both, increased metabolism of testosterone in adipose tissue and decreased testosterone production in the testes, are mechanisms by which obesity drives testosterone loss.…”
Section: Sex Differences In Obesitymentioning
confidence: 99%
“…Reactive oxygen species are associated with sperm DNA oxidative damage in humans and animal models (Bakos, Mitchell, Setchell, & Lane, 2011; Pearce, Hill, & Tremellen, 2019). Animal models suggest that increased oxidative stress is present in testicular tissue and expression of genes related to oxidative stress is also altered (Zhao, Zhai, Liu, Wu, & Xu, 2014). Other metabolites, such as aspartate, carnitine, myo‐inositol, and serine also showed similar changes in the testes of obese and 5'‐AMP‐treated lean mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mild diet restriction and supplementation with antioxidant rich foods or pure compounds were reported to protect obese subjects from oxidative stress and improve fertility (Roushandeh et al, 2015). Diet restricting an obese mutant of three age groups had metabolically beneficial effect, but (Erdemir et al, 2012;Jensen et al, 2004;Kort et al, 2006;MacDonald et al, 2010;Michalakis, Mintziori, Kaprara, Tarlatzis, & Goulis, 2013;Zhao, Zhai, Liu, Wu, & Xu, 2014). Further it was observed that mild diet restriction improved the duration of reproductively active periods in various animal models (Roushandeh et al, 2015;Suleiman, Ali, Zaki, EL-MALIK, & Nasr, 1996).…”
Section: Discussionmentioning
confidence: 99%